ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI PENDAPATAN SEKTOR INFORMAL USAHA ANGKRINGAN DI KOTA DENPASAR - Putra, I Gusti Ngurah Made Astika; Yasa, Dr. I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 10 (2023): Vol.12.No.10. OKTOBER 2023[650-724]DO - 10.24843/EEP.2023.v12.i10.p04, 2023)
This study aims to simultaneously or partially analyze multiple factors that affect the informal sector income of Angklingan enterprises in Denpasar city: working capital, working hours and business duration. All data for this study used primary data obtained by distributing questionnaires to 71 interviewees. Samples are determined by random sampling techniques. The analytical technique used is multiple regression analysis. As a result, it was found that working capital, working hours and operating period simultaneously had a significant impact on the informal sector income of Angklingan companies in Denpasar city. Variables such as working capital, working hours and length of operation have had some positive impact on the income of the informal business sector in Denpasar city..   keyword : Angkringan Business, Income, Working Capital, Working Hours, Length of Business